Ski touring in Poland: Who takes part in this form of specialised tourism? How do they take part and why? - Jażdżewska, Iwona (Turyzm/Tourism, 2016)
The article presents a description of ski touring by Polish tourists. The author is looking for answers to the following questions: Who goes on this form of tourism? How and why? How experienced are the tourists? Are they aware of the risks involved? Are they theoretically and practically prepared for the danger of avalanches? The author compares their social features and tourist-recreational behaviour to research conducted by the Central Statistical Office in 2012.